Diakoni som sekularingsringsindikator - Nielsen, Sune Wadskjær (Religionsvidenskabeligt Tidsskrift, 1999)
this article deals with secularization and Christian social work. It is a study of how the parish-based social work in St. John’s Parish in Aarhus has been influenced by the secularization process in Denmark. The major source material of the study is two journals containing summaries of all the meetings among the voluntary social workers in the parish in the period from 1905 to 1997. Karel Dobbelaere’s three dimensional secularization concept, which divides secularization into a societal, and institutional and an individual level, has been used in order to structure the material. Four major tendincies have been identified. 1) After the First world Ware there was a decrease in the need for help in St. John’s Parish and a stagnation in the recruitment of voluntary social workers, which suggests that secularization was increasing. 2) The period of the German occupation of Denmark was a sacralization phase, where there was progress in most areas of the social work. At this time the parish-based social work had a sectarian gemeinschaft-like attitude towards collaborating with other forms of public as well as voluntary work. 3) In the late fifties and the beginning of the sixties, the seculaarization trend was most predominant. the social work lost its nursing sister and recruitment was bad, probably because of the increasing number of women in the labour market. Traditionally, the voluntary social workers had mainly been recruited from among housewives, but they were now mobilized to participate in the booking Danish economy. 4) In the eighties and the nineties there has been a tendency towards sacralization. This is due to the employment of a professional parish worker in 1985, who could organize the activities of the voluntary social workers. It was the favourable economic situation of hte Danish Lutheran church which made it possible to employ a professional parish worker. Recruitment was still low in this period as the voluntary social workers seemed to prefer to collaborate with non-religious institutions. Some of these tendencies are probably general for the secularization provess in Denmark. they suggest that secularization in Denmark has not been a straight forward unilinear process.